The Yuanpei program in Peking University : A case study of curriculum innovation - Wang, Wanying (Springer Berlin Heidelberg, 2014)
This study explores the process of curriculum innovation-the Yuanpei Program, which is intended to provide general education at Peking University and offers key insights in terms of theory and practice.   First, it contributes to development of the understanding of curriculum innovation and the enrichment of knowledge on general education, its principles and practice in China. More specifically, it enriches the literature on the curriculum reform in higher education by describing the complexity of the process in the Chinese context. The conflict approach to examining the curriculum change has allowed the author to better understand the difficulty and constraints involved in the innovation. Many studies conducted before tend not to focus on conflicts and constraints in a systematic way, thus leaving many aspects to be investigated. The data on general education reforms practices obtained from the study will expand the understanding of general education reforms in the Mainland context.   Second, this study will provide a valuable reference work on reforms in higher education in China. The general education reforms, though conducted at several universities, are still in the trial stage. The lessons learned from the study illustrate what kinds of conflicts and problems might arise, supporting practitioners by addressing sources of conflicts that could be avoided or effectively defused.